Aim Sinpeng and Ross Tapsell, eds. From Grassroots Activism to Disinformation: Social Media in Southeast Asia. Singapore: ISEAS-Yusof Ishak Institute, 2021, 225 pp. - Marañon, Ia Denise Arnette (Archīum Ateneo, 2021)
Excerpt: At the onset of Rodrigo Duterte’s presidency in the Philippines, there were several attempts by those in the opposition to “promote” critical thinking to counter the disinformation happening in cyberspaces especially as a response to the electoral infrastructure established by the Duterte camp. What these efforts from the opposition overlook, however, is that while the experiences on social media are personal and individualized for some, the industry that underpins it is not. The book Grassroots Activism and Disinformation: Social Media in Southeast Asia repeatedly makes the claim that the industry behind social media movements and its governments in Southeast Asia—not necessarily backed or funded by these governments, but rather envelopes it—are a critical juncture for the use of social media in the future for both the citizenry and its governments.